Seek - Fleischman, Paul. (Chicago : Cricket Books, 2001)
Rob becomes obsessed with searching the airwaves for his long-gone father, a radio announcer.
"A Marcato book.".
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
7.1
Young Adult
Keywords: Fathers and sons -- Fiction; Radio -- Fiction; Father-son relationship -- Fiction; Radio -- Fiction